The dissolution of olivine added to soil at 32°C: the fate of weathering products and its implications for enhanced weathering at different temperatures - Iff, Nicholas; Renforth, Phil; Pogge von Strandmann, Philip A. E. (Frontiers in Climate, 2024)
The amendment of agricultural soils by crushed silicate minerals has been proposed to enhance weathering rates and facilitate carbon dioxide (CO2) removal from the atmosphere. Laboratory dissolution experiments regularly provide weathering rates that are significantly higher than those observed under natural conditions, while field studies are limited in the nature of data they can collect. This study uses an experimental setup that aims to encapsulate natural field conditions in a controlled setting using soil cores retrieved from UK cropland amended with crushed olivine at 32°C. Results are compared to previously run identical enhanced weathering experiments at 4°C (Pogge von Strandmann et al., 2022) and 19°C (Renforth et al., 2015). The experiments reveal temperature-dependent variations in the behaviour of different elements, most importantly Mg and Si, with silicon being retained at moderate temperatures and magnesium being retained at higher temperatures, most likely due to different retention mechanisms such as Si reprecipitation (e.g. as cation-depleted encapsulating Si layers) and cation exchange (affecting Mg, but to a lesser degree Si). The influence of cation exchange should be accounted for when interpreting enhanced weathering field data and measurements of (single) cations should not be used to quantify carbon sequestration. A temperature effect on the weathering rate of olivine added to soil columns is observed with the weathering rate being higher at 32°C than at 19°C and 4°C, and significantly lower than idealised laboratory-derived weathering rates, which emphasises the need for further enhanced weathering field trials, as simple laboratory-derived rates cannot be used to assess the feasibility of enhanced weathering measures. The weathering potential at 32°C is conservatively estimated at ~200 t CO2 km-2 yr-1 assuming an olivine amendment rate of 12.7 kg/m2. Our data suggests that soil accumulation of heavy metals like Cu and Cr at high temperatures (hence high weathering rates) is non-dangerous, however, Ni concentrations in the effluent solution are close to EU guidelines while Cr and Cu are considerably lower than guidelines. All of these conclusions have implications for the application of enhanced weathering for carbon dioxide removal from the atmosphere.